Gene Networks Underlying Cannabinoid and Terpenoid Accumulation in Cannabis. Issue 4 (28th May 2019) - Zager, Jordan J.; Lange, Iris; Srividya, Narayanan; Smith, Anthony; Lange, B. Markus
Abstract : Metabolite and transcriptome profiling of cannabis glandular trichomes differentiates strains and provides evidence for the coregulation of cannabinoid and terpenoid volatile biosynthesis Abstract: Glandular trichomes are specialized anatomical structures that accumulate secretions with important biological roles in plant-environment interactions. These secretions also have commercial uses in the flavor, fragrance, and pharmaceutical industries. The capitate-stalked glandular trichomes of Cannabis sativa (cannabis), situated on the surfaces of the bracts of the female flowers, are the primary site for the biosynthesis and storage of resins rich in cannabinoids and terpenoids. In this study, we profiled nine commercial cannabis strains with purportedly different attributes, such as taste, color, smell, and genetic origin. Glandular trichomes were isolated from each of these strains, and cell type-specific transcriptome data sets were acquired. Cannabinoids and terpenoids were quantified in flower buds. Statistical analyses indicated that these data sets enable the high-resolution differentiation of strains by providing complementary information. Integrative analyses revealed a coexpression network of genes involved in the biosynthesis of both cannabinoids and terpenoids from imported precursors. Terpene synthase genes involved in the biosynthesis of the major monoterpenes and sesquiterpenes routinely assayed by cannabis testing laboratories were identified and functionally evaluated. In addition to cloning variants of previously characterized genes, specifically CsTPS14CT [(−)-limonene synthase] and CsTPS15CT (β-myrcene synthase), we functionally evaluated genes that encode enzymes with activities not previously described in cannabis, namely CsTPS18VF and CsTPS19BL (nerolidol/linalool synthases), CsTPS16CC (germacrene B synthase), and CsTPS20CT (hedycaryol synthase). This study lays the groundwork for developing a better understanding of the complex chemistry and biochemistry underlying resin accumulation across commercial cannabis strains.